Labour market economics : a short survey of recent theory - Corina, John. (London : Heinemann Educational, 1972)
This brief book is a reproduction of a survey "of recent theories of the labour market" prepared by Dr. Corina for an SSRC Industrial Relations Conference at the University of Warwick in September 1971. Its focus is theoretical, reflected by the fact that less than 40 of the 231 references cited in the extremely useful bibliography are to British studies.
Bibliography: p. [68]-81.
rpm 17/04/2018
Loans
Keywords: Labor economics; Unemployment